Inferior epigastric pseudoaneurysm and rectus sheath hematoma treated with percutaneous direct sac puncture and embolization with NBCA - Jacob Schick, MD; David Gage, MD; Christopher Bailey, MD (Radiology Case Reports)
Rectus sheath hematomas are most commonly observed in elderly patients on anticoagulation and may require embolization when there is accompanying hemodynamic instability or vascular injury. We present a case of an inferior epigastric pseudoaneurysm and rectus sheath hematoma treated by percutaneous direct sac puncture with N‑butyl cyanoacrylate (NBCA) glue due to complex vascular anatomy and body habitus which limited an intra-arterial approach. While superficial pseudoaneurysms are often managed with thrombin, liquid embolics may offer improved penetration into the afferent and efferent supply of the pseudoaneurysm, thereby limiting re-bleeding risk.